Advanced Preparative Strategies for Activated Carbons Designed for the Adsorptive Storage of Hydrogen - A. Celzard; V. Fierro; J.F. Marêché; G. Furdin (Adsorption Science & Technology)
Since air quality is a major public health concern, especially in urban areas, the use of alternative fuels for vehicular applications has been strongly encouraged. Of these fuels, hydrogen is the only one that can produce zero emission through fuel cells. However, the storage of such a very light and highly combustible gas has yet to be solved. Only adsorption storage is discussed in the present paper. It should be recalled that no material has been capable of meeting the recommended targets to date. Recent progresses in preparing suitable carbon structures for hydrogen storage are described, and new routes for characterising and correspondingly improving the micropore texture are explored.